The Impact of Variant Allele Frequency in EGFR Mutated NSCLC Patients on Targeted Therapy - Friedlaender, Alex; Tsantoulis, Petros; Chevallier, Mathieu; De Vito, Claudio; Addeo, Alfredo (Frontiers in Oncology, 2021)
EGFR mutations represent the most common currently targetable oncogenic driver in non-small cell lung cancer. There has been tremendous progress in targeting this alteration over the course of the last decade, and third generation tyrosine kinase inhibitors offer previously unseen survival rates among these patients. Nonetheless, a better understanding is still needed, as roughly a third of patients do not benefit from targeted therapy and there is an important heterogeneity among responders. Allelic frequency, or the variant EGFR allele frequency, corresponds to the fraction of sequencing reads harbouring the mutation. The allelic fraction is influenced by the proportion of tumour cells in the sample, the presence of copy number alterations but also, most importantly, by the proportion of cells within the tumour that carry the mutation. Mutations that occur early in tumour evolution, often called clonal or truncal, have a higher allelic frequency than late, subclonal mutations, and are more often drivers of cancer evolution and attractive therapeutic targets. Most, but not all, EGFR mutations are clonal. Although an exact estimate of clonal proportion is hard to derive computationally, the allelic frequency is readily available to clinicians and could be a useful surrogate. We hypothesized that tumours with low allelic frequency of the EGFR mutation will respond less favourably to targeted treatment. In this article, we present a retrospective analysis of the impact of allelic frequency on survival in patients with EGFR mutant non-small cell lung cancer. We then combine allelic frequency with the presence of co-mutations, a known negative predictive factor for targeted therapy in this setting.